2002
DOI: 10.1063/1.1469680
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen storage in different carbon nanostructures

Abstract: Carbon nanostructures of different kinds have been synthesized by chemical vapor deposition. By modifying the deposition temperature, the catalyst material, and the hydrocarbon, nanofibers with herringbone structure, multi-walled nanotubes with tubular structure, and single-walled nanotubes were deposited. The nanostructures were purified with different treatment methods. The carbon nanostructures were characterized using scanning and transmission electron microscopy. The hydrogen storage capability was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(67 citation statements)
references
References 11 publications
3
64
0
Order By: Relevance
“…Some of the recent papers report hardly any adsorption in the different carbon nanostructures, the maximum adsorption in some cases being lower than 1 wt%. 15,16 In view of the importance of the subject and also the wide differences amongst the various findings, we considered it important to carry out H 2 adsorption measurements systematically on well-characterized samples of carbon nanotubes and fibres prepared by different methods. We have, therefore, carried out measurements on SWNTs produced by the arcdischarge method, on MWNTs synthesized by arc-discharge and by the pyrolysis of acetylene over catalysts, on aligned multi-walled nanotubes obtained by the pyrolysis of organometallic precursors as well as carbon fibres.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the recent papers report hardly any adsorption in the different carbon nanostructures, the maximum adsorption in some cases being lower than 1 wt%. 15,16 In view of the importance of the subject and also the wide differences amongst the various findings, we considered it important to carry out H 2 adsorption measurements systematically on well-characterized samples of carbon nanotubes and fibres prepared by different methods. We have, therefore, carried out measurements on SWNTs produced by the arcdischarge method, on MWNTs synthesized by arc-discharge and by the pyrolysis of acetylene over catalysts, on aligned multi-walled nanotubes obtained by the pyrolysis of organometallic precursors as well as carbon fibres.…”
Section: Introductionmentioning
confidence: 99%
“…Some time ago carbon nanotubes were suggested to be useful for storing hydrogen, but only ∼3 wt % storage has since been achieved (2)(3)(4). It has been shown that reaction of single-layer graphene with hydrogen atoms generates sp 3 C-H bonds on the basal plane and the reduced material gets dehydrogenated on photothermal heating (5).…”
mentioning
confidence: 99%
“…This result is consistent with many experiments, which reported that SWNTs have a certain hydrogen storage capacity at low temperature, [13][14][15] but have very low hydrogen uptake capacity at room temperature. [8][9][10][11][12] For H 2 molecules adsorbed on defected SWNTs, the situation is very different. Figure 7 shows a H 2 molecule stably adsorbed on the defected ͑10,10͒ SWNT at 300 K. Figure 7͑a͒ shows the radial distance of the adsorbed H 2 molecule from the adsorbing site on a defected ͑10,10͒ SWNT, versus annealing time at temperature, T = 300 K. It is obvious that this H 2 molecule is vibrating around its equilibrium distance without the trend of escaping from the tube in the time scale studied.…”
Section: B Adsorption Energies and Electron Density Contours Around mentioning
confidence: 98%
“…[5][6][7] In contrast to these reported promising results, other experimental measurements gave very discouraging results of hydrogen storage capacity in all examined carbon nanostructures, including SWNTs and MWNTs at room temperature. [8][9][10][11][12] Hydrogen storage in carbon nanotubes at low temperature and high pressure may be more suitable for obtaining higher hydrogen storage capacity. Hydrogen adsorption capacity more than 8 wt % in purified crystalline ropes of SWNTs was observed at ϳ128 atm and at 80 K. 13 A storage capacity of more than 6 wt % at T = 77 K and pressure 1 -2 atm for hydrogen physisorbed on heavily processed ropes of SWNTs was also reported.…”
Section: Introductionmentioning
confidence: 99%